2014
DOI: 10.1055/s-0034-1383261
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from Psychotria Target Sirtuins: In Silico and In Vitro Interaction Studies

Abstract: Epigenetic enzymes such as histone deacetylases play a crucial role in the development of ageing-related diseases. Among the 18 histone deacetylase isoforms found in humans, class III histone deacetylases, also known as sirtuins, seem to be promising targets for treating neurodegenerative conditions. Recently, Psychotria alkaloids, mainly monoterpene indoles, have been reported for their inhibitory properties against central nervous system cholinesterase and monoamine oxidase proteins. Given the multifunctiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The in silico results allowed for the selection of five potentially active compounds, 45 – 47 , 61 , and 62 . The sirtuin inhibition of these compounds was confirmed in vitro in a dose‐response manner, with preliminary information on their pharmacokinetics properties . Strictosidinic acid ( 24 ) decreased serotonin levels in rat hippocampus.…”
Section: Biological Activitiesmentioning
confidence: 85%
“…The in silico results allowed for the selection of five potentially active compounds, 45 – 47 , 61 , and 62 . The sirtuin inhibition of these compounds was confirmed in vitro in a dose‐response manner, with preliminary information on their pharmacokinetics properties . Strictosidinic acid ( 24 ) decreased serotonin levels in rat hippocampus.…”
Section: Biological Activitiesmentioning
confidence: 85%
“…acetylcholinesterase (AChE), butyrylcholinesterase (BChE), monoamine oxidase A (MAO-A), MAO-B, and catechol-O-methyltransferase (COMT) has been demonstrated. [4][5][6][7][8][9][10][11][12][13] In this sense, Psychotria is considered as an important source of active compounds…”
mentioning
confidence: 99%
“…The therapeutic potential of Psychotria has been linked to the presence of indole alkaloids 4,[6][7][8] and one important source is P. nemorosa Gardner. Recently, it was demonstrated that the alkaloid fraction obtained from the leaves of P. nemorosa significantly inhibited BChE and MAO-A activities.…”
mentioning
confidence: 99%
See 2 more Smart Citations